Exploring diazoxide and continuous glucose monitoring as treatment for Glut1 deficiency syndrome - Santhi N. Logel (Wiley, 2021)
Abstract Glut1 deficiency syndrome is caused by SLC2A1 mutations on chromosome 1p34.2 that impairs glucose transport across the blood–brain barrier resulting in hypoglycorrhachia and decreased fuel for brain metabolism. Neuroglycopenia causes a drug‐resistant metabolic epilepsy due to energy deficiency. Standard treatment for Glut1 deficiency syndrome is the ketogenic diet that decreases the demand for brain glucose by supplying ketones as alternative fuel. Treatment options are limited if patients fail the ketogenic diet. We present a case of successful diazoxide use with continuous glucose monitoring in a patient with Glut1 deficiency syndrome who did not respond to the ketogenic diet.